2020
DOI: 10.3390/nu12061872
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Analysis of Trigonelline Contained in Raphanus sativus Cv. Sakurajima Daikon and Results from the First Trial Examining Its Vasodilator Properties in Humans

Abstract: Vascular disease poses a major public health problem worldwide. Trigonelline isolated from Raphanus sativus cv. Sakurajima Daikon (Sakurajima radish) induces nitric oxide production from vascular endothelial cells and enhances vascular function. Here, we investigated the characteristics of trigonelline and its effects on endothelial function after consumption of Sakurajima radish by humans. Our results show that Sakurajima radish contains approximately 60 times more trigonelline than other radishes and squashe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…However, the preventive effect decreased when the mulberry leaves were roasted and when mulberry leaf extract was not added at the time of contraction despite exposure to mulberry leaves for a long time (60 h). The difference in the preventive effects of roasted and unroasted tea leaves can be attributed to the effect of the roasting process; for example, it is known that iminosaccharides 29 and trigonelline 11 are degraded during the roasting process and that high‐temperature drying decreases the antioxidant activity of mulberry leaves. 30 Therefore, roasting may have affected the degradation of key components of mulberry leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preventive effect decreased when the mulberry leaves were roasted and when mulberry leaf extract was not added at the time of contraction despite exposure to mulberry leaves for a long time (60 h). The difference in the preventive effects of roasted and unroasted tea leaves can be attributed to the effect of the roasting process; for example, it is known that iminosaccharides 29 and trigonelline 11 are degraded during the roasting process and that high‐temperature drying decreases the antioxidant activity of mulberry leaves. 30 Therefore, roasting may have affected the degradation of key components of mulberry leaves.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 For example, antioxidants in red wine have been suggested to have a functional effect on blood vessels. 9 Various other foods have been reported to regulate physiological functions, such as the vascular endothelial function‐improving effects of Sakurajima daikon ( Raphanus sativus “Sakurajima Daikon”) 10 , 11 and the antioxidant effects of Capsicum annuum . 12 Mulberry ( Morus australis Poir.)…”
Section: Introductionmentioning
confidence: 99%
“…I am pleased that 19 papers published in this Special Issue [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], present novel findings and adhere to the above-mentioned current trends. I personally consider the fact, that some papers in this issue also reported negative or only mild effects of the tested compounds to be very important as well.…”
mentioning
confidence: 83%
“…Human interventional studies published in this Special Issue included: (a) a study that found that riceberry rice bread rich in anthocyanins caused a significantly lower postprandial glucose peak in comparison to Hom Mali bread [ 11 ] and similarly, a polyphenol-rich functional food breakfast caused a lower glucose peak than ready-to-eat breakfast cereal [ 14 ]; (b) a comparison of the effect of beverages enriched with phenol-rich extracts from apple, blueberry, and coffee berry on cognition and mood [ 13 ]; (c) a study that found that Sakurajima radish administration did not reduce arterial blood pressure but showed a tendency to decrease heart rate [ 21 ]. An epidemiological study suggested, that intake of two groups of polyphenols (stilbenes and flavonoids) was associated with lower obesity prevalence.…”
mentioning
confidence: 99%
“…Ingestion of TRG-enriched Sakurajima radish (170 g/day, for 10 days) increased the plasma TRG levels and improved flow-mediated dilation, an index of vascular endothelial function [ 80 ].…”
Section: Cardiovascular Protection Effects Of Trgmentioning
confidence: 99%